Informe de Pasantía en la Dirección de Impuestos y Aduanas Nacionales-DIAN (2020)
The objective of this report is to describe the activities carried out during the internship at the DIAN in the area of customs management and inspection division; Accompanying in the processes of storage and verification of labeling, marking and reference of the goods apprehended by the POLFA, coming from abroad or goods that are not labeled from the country that comes from. Acts of apprehension were made, punctually describing the characteristics of the merchandise; responses were given to taxpayers who have pending cases in the entity; at the same time write minutes of return of merchandise when this occurs; On the other hand, I have an order of the apprehensions or cases that are kept in the control books that are handled. The objectives of the internship were met, applying the knowledge acquired during the race.